CFD analysis of swirly flow field in conical and cylindrical cyclones for deoiling applications - Nor, M.A.M. (Asian Research Publishing Network, 2016)
Hydrocyclone is a key purifying component in deoiling process as it is passive, requires low maintenance and has a small footprint. Many studies have been dedicated to the widely used design being the counter current cyclone. Concurrent on the other hand receives less attention and the geometrical shape studied only focuses on cylindrical body. To the author's knowledge, conical body has yet to be studied which prompted this investigation. In this study, numerical method using ANSYS FLUENT is employed to study the flow field differences of conical and cylindrical concurrent cyclones such as on tangential and axial velocities and recirculation region at 45° and 72° fluid swirl angles. Analyses have shown that conical cyclone increases average tangential velocity by 6.4 and 16.3 at 45° and 51.1 and 34.2 at 72° (sampled at 25 and 75 lengths respectively) compared to cylindrical one. Axial velocity improvements to the outlets of 58.8 and 32.1 at 45° and 58.9 and 62.9 at 72° on average are registered at 25 and 75 length respectively. Recirculation in conical is also thinner and shorter and the presence of reverse flow at the annulus outlet is not detected compared to cylindrical cyclone. These improvements are beneficial for droplet separation for achieving high efficiency. ©2006-2016 Asian Research Publishing Network (ARPN).